2015
DOI: 10.5539/gjhs.v8n6p14
|View full text |Cite
|
Sign up to set email alerts
|

The Nutrition and Dietetics Workforce Needs Skills and Expertise in the New York Metropolitan Area

Abstract: Background:There is an increased demand in the Nutrition and Dietetics field which has fostered credentialing to ensure competent graduates. The objective of this study is to conduct an exploratory analysis to identify nutrition/dietetics workforce needs, skills and expertise in the New York metropolitan area as exemplified in position announcements over a 4 year period.Methods:We recorded position announcements for jobs in nutrition and dietetics from the New York State Registered Dietitian Yahoo group, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…In addition, existing literature has identified a disconnection between Nutrition and Dietetics workplace demands and the content of existing educational curriculums and learning objectives taught across nutrition programs ( 14 , 15 ). Speculations that the same scenario may apply to public health programs exist, suggesting the need to examine the existing public health workforce demands and identify the extent to which they are being met by the existing curriculums utilized by schools and programs of public health.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, existing literature has identified a disconnection between Nutrition and Dietetics workplace demands and the content of existing educational curriculums and learning objectives taught across nutrition programs ( 14 , 15 ). Speculations that the same scenario may apply to public health programs exist, suggesting the need to examine the existing public health workforce demands and identify the extent to which they are being met by the existing curriculums utilized by schools and programs of public health.…”
Section: Discussionmentioning
confidence: 99%
“…This is reflected in a study that showed some gaps between the Nutrition and Dietetics workforce needs and the competencies of the nutrition program. 16 Future research is needed to map the public health competencies to the existing public health jobs and the necessary skills that public health professionals should acquire to address the various public health challenges in the 21 st century. The curriculum offered at the various public health institutes needs to be evaluated so that they adequately provide the public health professionals with the right tools to meet the changing demands of the public health workforce.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the public health informatics programs offered, population health informatics is a relatively recent advancement. Studies have shown that despite the growing volume of training programs in Informatics as well as public health, gaps exist in the competencies of public health graduates in meeting the requisite skills and demands of the dynamic public health workforce [2][3][4].…”
Section: Introductionmentioning
confidence: 99%